Protection of under ballast mats against damage Due to loads from railroad tracks - Remigiusz Duszyński (Przegląd Komunikacyjny)
Abstract: The paper presents the application of geogrids with uniform radial stiffness in subgrade structures in the function of protecting under ballast mats from damage caused by the railroad superstructure. The importance of the stabilizing function as a key mechanism of cooperation between geogrid and aggregate was pointed out, affecting the increase of subgrade bearing capacity, extension of ballast life and ensuring the required operating parameters of the ballast placed on anti-vibration mats. Keywords: Mechanical stabilization; Hexagonal geogrids; Under ballast mats; Railway trackbed